Social protection of non-standard workers and the self-employed during the pandemic country chapters: Belgium, France, Ireland, Italy, Lithuania, Portugal, Romania, Sweden - Slavina Spasova; Dalila Ghailani; Sebastiano Sabato; Bart Vanhercke (European Trade Union Institute (ETUI), 2021)
The Covid-19 pandemic severely affected some categories of non-standard workers, and particularly the self-employed. The emergency measures cushioned the potentially disastrous effect on their social circumstances, but undeniably highlighted even more the gaps in their access and entitlement to social protection benefits. While the first report of this joint project of the European Trade Union Institute (ETUI) and the European Social Observatory (OSE) mapped the measures taken in relation to unemployment benefits, sickness benefits and leave for non-standard workers and the self-employed (Spasova et al. 2021), this edited volume comprises eight country case studies: Belgium, France, Ireland, Italy, Lithuania, Portugal, Romania and Sweden. [...]
Keywords: 330; self-employed; atypical employment; coronavirus; Social Security; Belgium; France; Ireland; Italy; Lithuania; Portugal; Romania; Sweden; Selbstständige; Atypische Beschäftigung; Coronavirus; Soziale Sicherheit; Vergleich; Belgien; Frankreich; Irland; Italien; Litauen; Portugal; Rumänien; Schweden